ANALISIS PREFERENSI PEDAGANG KECIL TERHADAP LEMBAGA PEMBIAYAAN DAN POTENSI BAITUL MAAL WAT TAMWIL UNTUK MENGATASI PRAKTIK BANK THITHIL (Studi Kasus Pasar Segamas Purbalingga) - Safura, Wahida Nurul; fiah, Multi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study intend to analyze the preferences and needs of small vendors in choosing their financing sources as well to analyze the opportunities and constraints of Baitul Maal wat Tamwil to overcome Bank Thithil (Informal Financial Institution) In Segamas Market Purbalingga. The method used in this study is qualitative research method with phenomenological approach. The data for this study were collected using semi-structured interview technique with several informants. The results showed that there are several criteria required by small vendor customers from a financial institution. Those criteria are: low range loan, informal relationship between financial institution and customers, flexibility both in terms of time or installment payment, the rapid disbursement of funds, simple financing procedure and low interest. Based on those criteria, not only known that most informants prefer to make loans to Bank Thithil than BMT, but also can be said that BMT has the potential to overcome the practice of Bank Thithil in Segamas Market. Unfortunately, BMT having some problem while doing their financial activitie. Those problems are: BMT has not been able to establish a good personal relationship with the small vendor, small vendor’s lack of knowledge about BMT because most of them are not familiar with financial institutions on behalf of the institution but on behalf of individuals, although there are small vendors who already became the customer of BMT they still doing some transactions with Bank Thithil, and the last BMT can not fulfill the vendor’s need to simplify the process of financing installments. Keywords: Preferences, Bank Thithil, Micro Financial Institutions, and Baitul Maal Wat Tamwil